A novel COVID-19 program, delivering vaccines throughout rural and remote Australia - Gardiner, Fergus W.; Schofield, Zoe; Hendry, Miranda; Jones, Kate; Smallacombe, Mandy; Steere, Mardi; Beach, Jenny; MacIsaac, MaryBeth; Greenberg, Randall; Crawford, Candice; Trivett, Melanie; Morris, Judah; et al. (Frontiers in Public Health, 2023)
Background The Royal Flying Doctor Service of Australia (RFDS) established a unique SARS-CoV-2 vaccination program for vaccinating Australians that live in rural and remote areas. This paper describes the preparation and response phases of the RFDS response. Methods This study includes vaccinations conducted by the RFDS from 01 January 2021 until 31 December 2021 when vaccines were mandatory for work and social activities. Prior to each clinic, we conducted community consultation to determine site requirements, patient characteristics, expected vaccination numbers, and community transmission rates. Findings Ninety-five organizations requested support. The majority (n = 60; 63.2%) came from Aboriginal Community Controlled Health Organizations. Following consultation, 360 communities were approved for support. Actual vaccinations exceeded expectations (n = 70,827 vs. 49,407), with a concordance correlation coefficient of 0.88 (95% CI, 0.83, 0.93). Areas that reported healthcare workforce shortages during the preparation phase had the highest population proportion difference between expected and actual vaccinations. Areas that reported high vaccine hesitancy during the preparation phase had fewer than expected vaccines. There was a noticeable increase in vaccination rates in line with community outbreaks and positive polymerase chain reaction cases [r (41) = 0.35, p = 0.021]. Engagement with community leaders prior to clinic deployment was essential to provide a tailored response based on community expectations.